2018
DOI: 10.1016/j.prrv.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foetal and infant growth and body composition on respiratory outcomes in preterm-born children

Abstract: Body composition and growth outcomes of preterm-born subjects have been studied by many researchers. In general, preterm-born children have lower height and weight especially in infancy. Despite showing potential for catch-up growth, they continue to lag behind their term counterparts in adolescence and adulthood. The various methods of studying body composition and the differing gestations and ages at which it is assessed may go some way to explaining the inconsistent results observed in different studies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…In this study, we found positive associations between weight SDS at 6 months of age and FVC and negative associations of both weight SDS at 6 months and change in weight SDS from birth to 6 months with FEV1/FVC ratio and FEF25-75. These results are in line with several other studies reporting positive associations between postnatal growth variables and lung volumes, but negative associations with variables related to obstructive lung function [5][6][7]28]. There are several suggestions behind these findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we found positive associations between weight SDS at 6 months of age and FVC and negative associations of both weight SDS at 6 months and change in weight SDS from birth to 6 months with FEV1/FVC ratio and FEF25-75. These results are in line with several other studies reporting positive associations between postnatal growth variables and lung volumes, but negative associations with variables related to obstructive lung function [5][6][7]28]. There are several suggestions behind these findings.…”
Section: Discussionsupporting
confidence: 92%
“…The associations between anthropometric measures and later respiratory outcomes such as asthma and lung function have been examined by many. The results vary between study populations and both positive, negative and no associations have been reported, which may be due to different ages of follow-up and different definitions of exposures and outcomes [2,7] . In this study, we found positive associations between weight SDS at 6 months of age and FVC and negative associations of both weight SDS at 6 months and change in weight SDS from birth to 6 months with FEV1/FVC ratio and FEF25-75.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[23] However, there is a paucity of data regarding the relationship between height and lung growth and development. [24,25] The relationship between fetal length and fetal lung growth and development remains to be revealed. BPD is a developmental disorder of the lungs that occurs predominantly in premature infants.…”
Section: Discussionmentioning
confidence: 99%